Modification of HZSM-5 with Phosphotungstate, Silver, and Cobalt to Enhance Catalytic Reaction of Bioethanol to Bioethylene - Dhea Atika Risnawati; Nova Yoga Pradana; Rochmadi Rochmadi; Imam Prasetyo; Hardaning Pranamuda; Sugianto Tandio; Teguh Ariyanto; Daffa Dewa Saputra (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2026)
Developing an optimal catalyst formulation is a critical challenge in expanding sustainable ethylene production and utilization as a chemical intermediate product. Metal oxide impregnation (silver nitrate (AgNO3), cobalt nitrate (Co(NO3)2), and phosphotungstic acid (H3PW12O40)) was used to enhance the catalytic performance of HZSM-5 by increasing active sites and acidity. The preparation of the catalyst was performed by the impregnation of various metals and amounts of loading particles inside the pores of HZSM-5. The particles were impregnated by incipient wetness impregnation and followed by calcination to obtain Ag/HZSM-5, Co/HZSM-5, and W/HZSM-5 catalysts. Characterization techniques, including N2 adsorption-desorption, SEM, and XRD, were used to analyze the catalyst properties. Catalytic performance was evaluated in a packed-bed reactor under varying reaction conditions at WHSV 1.8 h-1. The aim of this research is to identify optimal catalyst formulations that exhibit superior activity in both conversion and selectivity towards ethylene production. Modified HZSM-5 catalysts incorporating Ag, Co, and W exhibited enhanced catalytic performance for bioethanol dehydration to bioethylene, attributed to optimized acidic sites, pore structure, and metal synergy. The 1%W/HZSM-5 catalyst demonstrated superior ethylene conversion (98.2%) and selectivity (99.88%) at 300 ℃. Increasing tungsten loading up to 2% impacted the conversion of bioethanol. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).